Space within the Scientific Discourse for the Voice of the Other? Expressions of Community Voice in the Scientific Discourse of Community-Based Participatory Research. Issue 5 (15th April 2020) - Chandanabhumma, P. Paul; Duran, Bonnie M.; Peterson, Jeffery C.; Pearson, Cynthia R.; Oetzel, John G.; Dutta, Mohan J.; Wallerstein, Nina B.
ABSTRACT: Community-based participatory research (CBPR) has captured public health attention and support because it is positioned as an approach that involves researchers and communities as equitable partners in addressing health disparities. However, it is unknown the extent to which CBPR creates a participatory space in the scientific discourse to signal "community voice, " which we define as textual expression of community-centered perspectives on collective roles, interests, and worldviews. In this study, we utilized the culture-centered approach to examine the expression of community voice in the abstracts and public health relevance statements of 253 extramural CBPR projects in the U.S. that received funding from the National Institute of Health and Centers for Disease Control and Prevention in 2009. We found that project abstracts and public health relevance statements contain four textual domains, or potential sites of contest to signal the articulation of community agency and voice within the CBPR projects. These domains include: 1) the rationale for the community health issue, 2) the roles of community partners, 3) community-centered outcomes of the partnership, and 4) elements of participatory research process. The degree of culture-centeredness of the texts is suggested in the extent to which articulations of community agency and voice are signaled across the four domains. We conclude that the dynamics of CBPR may shape culture-centered expressions of problem identification, solution configuration, structural transformations, reflexivity, values, and agency in the project abstracts and public health relevance statements.